Video Blogging (Vlogging) to Enhance Students’ Speaking Skill of IAI Ibrahimy Genteng Banyuwangi - Mufidah Yusroh; Mohammad Erlangga (JOEY: Journal of English Ibrahimy, 2023)
This research was aimed to enhance students’ speaking performance by using vlog of the 1st semester Islamic Law students of IAI Ibrahimy Genteng Banyuwangi 2021/2022 Academic Year especially on Class A and B. It was focused to improve their speaking ability by using video blogging (vlog) as media. The research design of this study was a classroom action research. The 38 students of class A and B were participating in this research. The researcher observed the students’ improvement in speaking by collecting data through observation checklist, field notes and speaking performance by making a vlog. Based on the data, the students showed improvement in the process of speaking. In the cycle I, they were already great in making a vlog content but some of the students were still making some pauses and wrong pronounciation. Thus, the researcher conducted the cycle II which resulted that the students could speak more fluently and accurately and some of them gained good scores. It was proven that the mean score in cycle 1 of Class A was 73.92 and it was increased 78.57 in cycle 2. Whereas, the mean score of Class B in cycle 1 and cycle 2 was 76. There was no improvement but the criteria of success were achieved. By using vlog as media in enhancing students speaking performance, they got motivation to speak during the teaching and learning activity. Thus, based on the result, it can be inferred that vlog could enhance students’ speaking performance.